BUDGET FORECAST ERRORS AND BUDGET DEVIATION: FINANCIAL CAPABILITY INDEX AS MODERATING VARIABLE - Patty, Jancen Roland (Jurnal Tata Kelola dan Akuntabilitas Keuangan Negara, 2019)
The lack of accounting literature that links budget supervision or control with budget realization allows the author to conduct this study. In addition, the main issue of this study is the failure of the local government in planning, implementing and being responsible for the budget resulting in budget surpluses and deficits. Surplus and deficit prove the existence of the budget deviations. The cause of the budget deviation is a mistake in the budget forecast. Some cases of budget deficits in Indonesia prove this. Budget forecast errors have the potential to increase budget deviation due to the role of the financial capability index. The purpose of this study is to examine the role of financial capability index in influencing the relationship of budget forecast errors and budget deviation. The sample used local government in Indonesia between 2016 and 2018 through a purposive sampling technique. Analytical tools use STATA Version 15.1. The results of the study prove that budget forecast errors have a positive and significant effect on budget deviation, and the financial capability index has a positive effect on the relationship between budget forecast errors and budget deviation. Sensitivity testing and additional testing reinforced the initial testing of this study.